Proving a statement by contrapositive means that if you want to prove that [tex] A \implies B [/tex], you can instead prove that [tex] \neg B \implies \neg A [/tex] since the two are equivalent.
So, proving that [tex] n^2 \text{ is odd} \implies n \text{ is odd}[/tex] by contrapositive means to prove that
[tex] n \text{ is even} \implies n^2 \text{ is even}[/tex]
since of course the negation of being odd is being even.
This claim is quite easy to prove: if n is even, then it is twice some other integer k: [tex] n=2k [/tex]
This means that its square is [tex] n^2 = 4k^2 = 2(2k^2) [/tex]
And so, if n is even, its square is also even. This proves, by contrapositive, that if n squared is odd, then n is odd.